Pelestarian Tradisi Rejung Sebagai Warisan Budaya Lokal: Studi Desa Air Teras Kecamatan Talo Kabupaten Seluma - Setiani, Dwiza; Riswanto (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Tadulako, 2025)
This study aims to determine the preservation of the rejung tradition as a local cultural heritage: a study of the role of customary stakeholders in Air Teras Village, Talo District, Seluma Regency. The method used is qualitative with data collection techniques through observation, interviews and documentation. The theory used is symbolic interaction theory according to George Herbert Mead (mind, self, society). Mind in the research, traditional leaders conduct cultural socialization activities by using local language in explaining rejung as a symbol and language of local culture, connecting the meaning of rejung with social reality. Self (self), traditional leaders conduct direct social interactions in shaping the identity (sefl) of the younger generation by directly involving them in training activities and cultural activities. Society involves the younger generation in various cultural activities and cultural competitions that will strengthen the role of the younger generation as cultural preservationists.